THE STUDENTS’ ATTITUDE TOWARDS ENGLISH CLASSROOM ENVIRONMENT AT SMP KARTIKA BANJARMASIN SCHOOL YEAR 2014/2015 - Maulida, Hidya (Jurnal Humaniora Teknologi, 2015)
This research aims to find out the students’ attitude toward English classroom environment especially English teacher, English material and English classroom management. This research used descriptive method to find out the students attitude toward English teacher, English material and English classroom management.The population of this research was the ninth year students of SMP Kartika Banjarmasin which consists of two classes so the totalis 67 students. The instrument of the research was questionnaire by using mean score to find out the mean score of them.The result of the data analysis of the questionnaire indicated that the students have positive attitude toward English teacher (59.80), the students have positive attitude toward English material (59) and the students have positive attitude toward English classroom management (55.92).Based on the result, some suggestions are proposed: (1)Generally, the student's attitude toward English classroom environment is positive but there are still some students have neutral attitude so that its suggested to English teacher at the SMP Kartika Banjarmasin in order to learn more skills and pay attention to the classroom environment’s factor and he should be creative in teaching English so that the students can be motivated in learning English (2) To the students, they should make English as interesting subject so that it can give benefit to the future.